2003
DOI: 10.1046/j.1523-1755.2003.08809.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indices of in vivo biocompatibility: The role of ex vivo cell function studies and effluent markers in peritoneal dialysis patients

Abstract: Clinical indices of in vivo biocompatibility: The role of ex vivo cell function studies and effluent markers in peritoneal dialysis patients. Over the past 20 years, studies of the biocompatibility profile of peritoneal dialysis solutions (PDF) have evolved from initial in vitro studies assessing the impact of solutions on leukocyte function to evaluations of mesothelial cell behavior. More recent biocompatibility evaluations have involved assessments of the impact of PDF on membrane integrity and cell functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 89 publications
1
23
0
10
Order By: Relevance
“…Our results in this PD pilot trial are concordant with data from a recent first-in-man trial that described significantly enhanced LPS-stimulated cytokine release from peripheral blood mononuclear cells following incubation in PD effluent from patients treated with AlaGln 33 . Interestingly, the relative effects of AlaGln-supplementation on cytokine responses in these trials appeared comparable to those previously reported (between 70 and 260%) comparing double-chamber bag PDF to a standard single-chamber bag PDF 6, 11, 22, 23, 26 . Infection rates and patient outcomes among the critically ill are known to deteriorate in parallel with glutamine depletion and improve upon glutamine supplementation 20, 34–36 .…”
Section: Discussionsupporting
confidence: 85%
“…Our results in this PD pilot trial are concordant with data from a recent first-in-man trial that described significantly enhanced LPS-stimulated cytokine release from peripheral blood mononuclear cells following incubation in PD effluent from patients treated with AlaGln 33 . Interestingly, the relative effects of AlaGln-supplementation on cytokine responses in these trials appeared comparable to those previously reported (between 70 and 260%) comparing double-chamber bag PDF to a standard single-chamber bag PDF 6, 11, 22, 23, 26 . Infection rates and patient outcomes among the critically ill are known to deteriorate in parallel with glutamine depletion and improve upon glutamine supplementation 20, 34–36 .…”
Section: Discussionsupporting
confidence: 85%
“…This is supported by a number of in vitro and ex vivo studies that have demonstrated improvement in cellular function, in particular in the host immune system and an increase in markers of membrane integrity with their use [9, 10, 23, 24]. Peritonitis is an important cause of higher technique failure in Australia and New Zealand [4] and has been associated with greater mortality [5].…”
Section: Peritonitismentioning
confidence: 99%
“…Minimisation of GDP formation has been achieved through the development of the multicompartment bag system which allows for heat sterilisation and storage to occur at a low pH [22] and the use of bicarbonate buffer system to lower exposure to lactate. A number of in vitro and ex vivo studies have demonstrated improvement in cellular function, in particular in the host immune system and an increase in markers of membrane integrity [9, 10, 23, 24]. Animal studies have shown improvement in ultrafiltration capacity, lower vascular endothelial growth factor (VEGF) expression, vascular density, AGE accumulation, and fibrosis with its use [20, 25].…”
Section: Introductionmentioning
confidence: 99%
“…These adverse sequelae may be obviated by the administration of commercially available biocompatible PD solutions, characterized by neutral pH and low glucose degradation product (GDP) content. In vitro and ex vivo studies have observed significant improvements in peritoneal membrane cellular function and integrity after exposure to biocompatible solutions compared with conventional solutions (5,(9)(10)(11), and observational cohort studies have reported superior inflammatory marker levels (12), peritonitis and exit site infection rates (13), and patient survival (14)(15)(16). However, these clinical studies were limited by singlecenter design, small patient numbers (12,13), potential indication bias, center effects, and exclusion of patients treated with automatic peritoneal dialysis (15,16).…”
Section: Introductionmentioning
confidence: 99%